2016
DOI: 10.3390/su8080729
|View full text |Cite
|
Sign up to set email alerts
|

Network Analysis of Open Innovation

Abstract: Abstract:The way people innovate and create new ideas and bring them to the market is undergoing a fundamental change from closed innovation to open innovation. Why and how do firms perform open innovation? Firms' open innovation is measured through the levels of firms' joint patent applications. Next, we analyze network structures and characters of firms' joint patent applications such as betweenness and degree centrality, structure hole, and closure. From this research, we drew conclusions as follows. First,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 116 publications
1
19
0
1
Order By: Relevance
“…As the industrial economy changes to a knowledge-based economy, collaboration ratios are increasing for patent applications, R&D activities, and new product developments [22,23]. In Finland, through motivating collaborative patents, the development of a knowledge-based economy is encouraged [24].…”
Section: Research Scope and Methodsmentioning
confidence: 99%
“…As the industrial economy changes to a knowledge-based economy, collaboration ratios are increasing for patent applications, R&D activities, and new product developments [22,23]. In Finland, through motivating collaborative patents, the development of a knowledge-based economy is encouraged [24].…”
Section: Research Scope and Methodsmentioning
confidence: 99%
“…They find that the performance of companies has an inverted-U shape relationship with inbound practices and a clearly decreasing one with outbound ones. Yun et al [48] found that the structure of collaboration networks has both direct and indirect effects on firms' innovative performance. Rangus et al [49] examined how absorptive capacity and open innovation interact to impact innovation performance, reaching the conclusion that absorptive capacity mediates the relationship between open innovation and innovation performance.…”
Section: Open Innovation and Determinants Of Cooperation Formmentioning
confidence: 99%
“…Firstly, factors for dismantling the inverted U-Curve of open innovation were analyzed in relation to the open innovation network perspective [57][58][59]. Secondly, effective incentive design to reduce food waste was analyzed through a natural experiment of policy change from a community-based charge to a radio-frequency identification-based (RFID) weight charge, in relation to the RFID open innovation perspective [60,61].…”
Section: Sustainability Of Economic Growth: Combining Technology Marmentioning
confidence: 99%